Biomphalaria snails in East Africa’s river systems: distribution, genetics and schistosome infections - Onyango, Victor Magero (2024)
The population genetic structure of Biomphalaria snails was investigated. The degree of genetic variation and genetic population differentiation of Biomphalaria populations was inferred from the CO1 gene and the ITS-2 region. Phylogenetic relationships among the populations were deduced by PhyML version 2.4.4 using the Maximum Likelihood method, the GTR+G model, and with bootstrap values based on 1000 replicates. Measures of population differentiation were then calculated from CO1 sequence data and ITS-2 sequence data by use of the AMOVA model in Arlequin software version 3.5. The taxa identified were the ‘B. pfeifferi group’ and the ‘Nilotic Species Complex.’ AMOVA revealed low genetic variation within B. pfeifferi populations (between 4.83% and 5.86%) and high genetic differentiation among the populations (between 94.14% and 95.17%). As for the ‘Nilotic Species Complex’ individuals, the genetic diversity within populations was moderate (between 28.78% and 72.17%) so was the genetic differentiation among populations (between 27.83% and 49.74%). There was a clear geographical clustering of haplotypes with the identification of 18 B. pfeifferi CO1 haplotypes and 20 CO1 haplotypes for the ‘Nilotic Species Complex’ individuals. As for ITS-2 sequence data, there was identification of 27 B. pfeifferi ITS-2 haplotypes and 23 haplotypes for the ‘Nilotic Species Complex’ individuals.